Examining the Evidence for Regulated and Programmed Cell Death in Cyanobacteria. How Significant Are Different Forms of Cell Death in Cyanobacteria Population Dynamics? - Franklin, Daniel J. (Frontiers in Microbiology, 2021)
Please see MS